2022
DOI: 10.3390/bios12060419
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Fabrication of Fluorescent Hydroxyapatite for Cancer Cell Imaging and Bio-Printing Applications

Abstract: Hydroxyapatite (HAP) materials are widely applied as biomedical materials due to their stable performance, low cost, good biocompatibility and biodegradability. Here, a green, fast and efficient strategy was designed to construct a fluorescent nanosystem for cell imaging and drug delivery based on polyethyleneimine (PEI) and functionalized HAP via simple physical adsorption. First, HAP nanorods were functionalized with riboflavin sodium phosphate (HE) to provide them with fluorescence properties based on ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In this case, nanorods of HAp were functionalized with riboflavin sodium phosphate (HE) for the fluorescent properties, and subsequently, polyethyleneimine (PEI) was attached by electrostatic attraction. NIH-3T3 fibroblasts were treated with the nanocomposites and a fast uptake was reported, allowing correct cell imaging manifested with green fluorescence [ 157 ].…”
Section: Hap For Cancer Detection and Cell Imagingmentioning
confidence: 99%
“…In this case, nanorods of HAp were functionalized with riboflavin sodium phosphate (HE) for the fluorescent properties, and subsequently, polyethyleneimine (PEI) was attached by electrostatic attraction. NIH-3T3 fibroblasts were treated with the nanocomposites and a fast uptake was reported, allowing correct cell imaging manifested with green fluorescence [ 157 ].…”
Section: Hap For Cancer Detection and Cell Imagingmentioning
confidence: 99%
“…Hydroxyapatite (HAp, Ca 5 (PO 4 ) 3 OH) is the most abundant inorganic material in the mammalian bodies, where it forms hard tissues, including bone, enamel, dentin and cementum, but also other organs, including tusks in animals such as elephants or narwhals, horns in deer, moose, elks and caribous, and the shell-like osteoderm of armadillos [ 16 ]. Despite being one of the oldest biomaterials in research and clinical application, HAp continues to attract the attention of researchers to this day, and new studies on it do not abate [ 17 , 18 , 19 ]. Recently, our group demonstrated that HAp displays finite antibacterial properties, which appear to become intensified when the bacterial species are converted from regular lab strains to clinical, multidrug-resistant ones [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HAP) materials are widely used in biomedical materials because of their excellent properties, stable performance, low cost, good biocompatibility, and biodegradability. An efficient fluorescent nanosystem for cell imaging and drug therapy has been developed based on polyethyleneimine (PEI) and functionalized HAP delivered via simple physical adsorption [ 5 ]. The HAP nanorods were first functionalized using sodium riboflavin phosphate (HE) to give fluorescent properties based on a ligand exchange process.…”
mentioning
confidence: 99%
“…Next, PEI was attached to the surface through electrostatic attraction to functionalized HAP. The nanosystem can be rapidly taken up by NIH-3T3 fibroblasts and successfully applied for cell culture imaging [ 5 ]. In addition, the in vitro release results of Adriamycin hydrochloride (DOX) containing HAP-HE@PEI at high loading showed that DOX released the maximum amount of the drug at pH 5.4 (31.83%), significantly higher than that at pH 7.2 (9.90%), meaning that it can be used as a drug delivery tool.…”
mentioning
confidence: 99%
See 1 more Smart Citation